Electromagnetics - Rothwell, Edward J.; Cloud, Michael J. (CRC Press, 2009)
The book provides a firm grounding in the fundamental concepts of electromagnetics and bolsters understanding through the use of classic examples in shielding, transmission lines, waveguides, propagation through various media, radiation, antennas, and scattering. Mathematical appendices present helpful background information in the areas of Fourier transforms, dyadics, and boundary value problems. The second edition adds a new and extensive chapter on integral equation methods with applications to guided waves, antennas, and scattering